Pengaruh Sistem Informasi Akuntansi Berbasis Artificiall Intelligence Terhadap Kinerja Karyawan (Studi Pada PT Bank Syariah Indonesia Tbk di Kota Langsa) - Indi Yunita; Tuti Meutia; Iqlima Azhar (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
The research was conducted with the aim of finding out the effect of human resource competence, artificial intelligence-based accounting information systems on employee performance (study at PT Bank Syariah Indonesia Tbk in Langsa City). This type of research is quantitative, the data source used is primary data. The population and sample for this research are employees at PT Bank Syariah Indonesia Tbk in Langsa City, totaling 120 people as the population, and 96 respondents as the sample in this research. The data obtained was analyzed using SPSS (Statistical Package For Social Sciences) analysis techniques. The equation model analyzed is multiple linear regression analysis, classical assumption testing and hypothesis testing (T test, F test and coefficient of determination (R2)). The research results show that partially human resource competency, artificial intelligence-based accounting information systems have a significant positive effect on employee performance. Simultaneously, all independent variables, namely human resource competency, artificial intelligence-based accounting information systems together have a significant positive influence on employee performance. The limitations of this research are only limited to discussing human resource competencies, artificial intelligence-based accounting information systems on employee performance. Research should be developed with various other variables to find out how other variables influence employee performance. It is recommended that future researchers conduct research on different types of companies or different locations and add other variables that influence employee performance.